452 Patient Factors and Preferences in Decision for Sleep Surgery: A Qualitative Analysis. (3rd May 2021) - Ikeda, Allison; Marsh, Robin; McShay, Crystina; Saini, Shireen; Sardesai, Maya; Weaver, Edward; Boss, Emily
Abstract: Introduction: Patients with obstructive sleep apnea (OSA) are offered many treatment options spanning the spectrum of lifestyle modification, device therapy, and surgery. Sleep surgery, while often effective, results in moderate morbidity and has variable effectiveness on OSA improvement. Little is known about what patients consider when choosing treatment. We aim to identify factors that influenced the decision for sleep surgery among adults with OSA. Methods: We conducted semi-structured virtual interviews with patients (≥18 years) with OSA (apnea-hypopnea index ≥5 events per hour of sleep) who underwent sleep surgery at a tertiary academic center, querying patients about factors in their decision for OSA treatment. Interviews were audio-recorded, transcribed, and analyzed for thematic content. We anticipate enrolling 10–18 total participants based on previously reported sample size in specialty groups for thematic saturation in specialty groups (ie, when no new concepts or factors emerge from interviews). Here we report pilot qualitative analysis results. Results: Of nine eligible patients, eight enrolled (mean +/- standard deviation age 45.8 +/- 13.4 years, 2 female/6 males). Four patients underwent nasal surgery only, two patients underwent staged procedures, one underwent pharyngeal surgery only, and the last underwent nasal surgery with tori removal. Patients reported decision making duration of days to years for scheduling surgery. Reasons for pursuing sleep surgery included fatigue, quality of life, work performance, and safety. Overarching thematic domains related to decision for surgery were (1) major concerns, (2) external factors influencing decision, and (3) retrospective satisfaction/regret with decision. Major concerns involved factors beyond surgeon's control, such as anesthesia and postoperative pain management, not surgery itself. Family and friends were reported to be highly influential in the process, both in favor and against surgery. Social media features and celebrity patients with OSA heightened awareness of sleep surgery and set preconceived expectations. Patients were mostly satisfied with outcomes, despite unanticipated acute recovery challenges. Conclusion: This pilot qualitative analysis identifies factors influencing patients' OSA treatment decisions. Understanding patients' major concerns and sources of information may help to guide physician counseling, set realistic expectations, offer peri-operative support, and better engage parents in shared decision-making for sleep surgery. Support (if any): None.